2010
DOI: 10.1037/a0018422
|View full text |Cite
|
Sign up to set email alerts
|

Embodied auditory perception: The emotional impact of approaching and receding sound sources.

Abstract: Research has shown the existence of perceptual and neural bias toward sounds perceived as sources approaching versus receding a listener. It has been suggested that a greater biological salience of approaching auditory sources may account for these effects. In addition, these effects may hold only for those sources critical for our survival. In the present study, we bring support to these hypotheses by quantifying the emotional responses to different sounds with changing intensity patterns. In 2 experiments, p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
72
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 99 publications
(78 citation statements)
references
References 63 publications
6
72
0
Order By: Relevance
“…This effect was also demonstrated with tones, chords and vowels stimuli lasting 1.8 and 3.6 s (Olsen, Stevens, & Tardieu, 2010;. Neuroscience and psychophysiological experiments on humans showed that rising-intensity tonal stimuli from 750 ms to 2 s produce neural activity in the amygdala, recruit specific attentional and physiological resources and induce higher emotional ratings compared to falling-intensity sounds (Bach et al, 2008;Bach, Neuhoff, Perrig, & Seifritz, 2009;Seifritz et al, 2002;Tajadura-Jiménez, Väljamäe, Asutay, & Västfjäll, 2010). Similar results are observed in non-human primates, for whom behavioral and neural differences are also found between the two types of stimuli (Ghazanfar, Neuhoff, & Logothetis, 2002;Maier & Ghazanfar, 2007).…”
Section: Introductionmentioning
confidence: 91%
“…This effect was also demonstrated with tones, chords and vowels stimuli lasting 1.8 and 3.6 s (Olsen, Stevens, & Tardieu, 2010;. Neuroscience and psychophysiological experiments on humans showed that rising-intensity tonal stimuli from 750 ms to 2 s produce neural activity in the amygdala, recruit specific attentional and physiological resources and induce higher emotional ratings compared to falling-intensity sounds (Bach et al, 2008;Bach, Neuhoff, Perrig, & Seifritz, 2009;Seifritz et al, 2002;Tajadura-Jiménez, Väljamäe, Asutay, & Västfjäll, 2010). Similar results are observed in non-human primates, for whom behavioral and neural differences are also found between the two types of stimuli (Ghazanfar, Neuhoff, & Logothetis, 2002;Maier & Ghazanfar, 2007).…”
Section: Introductionmentioning
confidence: 91%
“…Several studies have shown increased autonomic nervous system responses to looming sounds consistent with a protective mechanism (Bach et al, 2009; Fletcher et al, 2015; Tajadura-Jimenez, Valjamae, Asutay, & Vastfjall, 2010). If the decision to engage the motor system in the face of a looming sound source was entirely under conscious control, then anyone engaged with a high cognitive load at the time would be disadvantaged in that there would be fewer cognitive resources to devote to the approaching danger.…”
Section: Resultsmentioning
confidence: 98%
“…Approaching unpleasant sounds trigger a particularly intense emotional response suggesting an activation of defensive responses (16). Previous results demonstrated that at distances wherein individuals non-sensitive to cynophobia still feel comfortable, a virtual visual looming dog triggers high discomfort for individuals sensitive to cynophobia (17).…”
Section: Discussionmentioning
confidence: 99%